Nomenclatural Studies Toward a World List of Diptera Genus-Group Names. Part V: Pierre-Justin-Marie Macquart - Evenhuis, Neal L.; Pape, Thomas; Pont, Adrian C. (Zootaxa, 2016)
The Diptera genus-group names of Pierre-Justin-Marie Macquart are reviewed and annotated. A total of 399 available genus-group names in 69 families of Diptera are listed alphabetically, for each name giving author, year and page of original publication, originally included species, type species and method of fixation, current status of the name, family placement, and a list of any emendations of it that have been found in the literature. Remarks are given to clarify nomenclatural or taxonomic information. In addition, an index to all the species-group names of Diptera proposed by Macquart (3,611, of which 3,543 are available) is given with bibliographic reference (year and page) to each original citation. The following type species are designated herein: Agculocera nigra Macquart, 1855 for Onuxicera Macquart, 1855, present designation [Tachinidae]; Trixa imhoffi Macquart, 1834, for Semiomyia Macquart, 1848, present designation [Tachinidae]. The following type species are designated herein with fixation under ICZN Code Art. 70.3.2: Azelia nebulosa Robineau-Desvoidy, 1830 for Atomogaster Macquart, 1835, present designation [Muscidae]; Tachydromia vocatoria Fallén, 1816 for Chelipoda Macquart, 1835, present designation [Empididae]; Eriocera macquarti Enderlein, 1912 for Eriocera Macquart, 1838, present designation [Limoniidae]; Limosina acutangula Zetterstedt, 1847 for Heteroptera Macquart, 1835, present designation [Sphaeroceridae]; Phryxe pavoniae Robineau-Desvoidy, 1830 for Masicera Macquart, 1834, present designation [Tachinidae]; Pachymyia macquartii Townsend, 1916 for Pachymyia Macquart, 1844, present designation [Tachinidae]. Earlier valid subsequent type-species designations have been found in this study for the following: Anisophysa Macquart, 1835 [Sepsidae]; Diphysa Macquart, 1838 [Stratiomyidae]; Pachyrhina Macquart, 1834 [Tipulidae]; Silbomyia Macquart, 1844 [Calliphoridae]. One name is raised from synonymy: Czernyola Bezzi, 1907, n. stat. [Clusiidae]. Names previously treated as available but found in this work to be unavailable include the following: Genus-group names—Anodontina Macquart, 1838, n. stat. [Empididae]; Athricia Macquart, 1834, n. stat. [Tachinidae]; Blepharis Macquart, 1838, n. stat. [Asilidae]; Dichelocera Enderlein, 1922, n. stat. [Tabanidae]; Lepidoselaga Loew, 1869, n. stat. [Tabanidae]; Lemptopeza Macquart, 1828, n. stat. [Hybotidae]; Microphora Zetterstedt, 1842, n. stat. [Dolichopodidae]; Microphorus Macquart, 1834, n. stat. [Dolichopodidae]; Plagiocephala Macquart, 1844, n. stat. [Ulidiidae]; Stratiomyia Macquart, 1838, n. stat. [Stratiomyidae]; Taenioptera Agassiz, 1846, n. stat. [Micropezidae]; Tapigaster Bezzi, 1923, n. stat. [Heleomyzidae]; Trizota Macquart, 1829, n. stat. [Syrphidae]. Species-group names—Microstylum sinense Macquart, 1838, n. stat. [Asilidae]. Corrected or clarified included species and/or corrected or clarified type-species and methods of typification are given for: Anabarhynchus Macquart, 1848 [Therevidae]; Anacanthella Macquart, 1855 [Stratiomyidae]; Apeilesis Macquart, 1846 [Tipulidae]; Aplomera Macquart, 1838 [Empididae]; Aprotheca Macquart, 1851 [Tachinidae]; Ardoptera Macquart, 1828 [Empididae]; Blepharella Macquart, 1851 [Tachinidae]; Brachystylum Macquart, 1855 [Tachinidae]; Cadicera Macquart, 1855 [Tabanidae]; Calobatemyia Macquart, 1855 [Calliphoridae]; Catapicephala Macquart, 1851 [Calliphoridae]; Ceroptera Macquart, 1835 [Sphaeroceridae]; Cheligaster Macquart, 1835 [Sepsidae]; Chetogaster Macquart, 1851 [Tachinidae]; Chlorogaster Macquart, 1851 [Tachinidae]; Cleitamia Macquart, 1835 [Platystomatidae]; Craspedia Macquart, 1838 [Asilidae]; Craspedochoeta Macquart, 1851 [Anthomyiidae]; Crumomyia Macquart, 1835 [Sphaeroceridae]; Dasyomma Macquart, 1840 [Athericidae]; Demoticus Macquart, 1854 [Tachinidae]; Epicerella Macquart, 1851 [Pyrgotidae]; Epicerina Macquart, 1850 [Acroceridae]; Euprosopia Macquart, 1847 [Platystomatidae]; Grapholostylum Macquart, 1851 [Tachinidae]; Graphomyzina Macquart, 1835 [Sciomyzidae]; Gymnostylina Macquart, 1835 [Tachinidae]; Heterometopia Macquart, 1846 [Tachinidae]; Laxenecera Macquart, 1838 [Asilidae]; Leptomyza Macquart, 1835 [Anthomyzidae]; Megistogaster Macquart, 1851 [Tachinidae]; Microtrichodes Macquart, 1846 [Tachinidae]; Microtropesa Macquart, 1846 [Tachinidae]; Ogcodocera Macquart, 1840 [Bombyliidae]; Onuxicera Macquart, 1855 [Tachinidae]; Ozodicera Macquart, 1834 [Tipulidae]; Pachymerina Macquart, 1834 [Empididae]; Pachyrhina Macquart, 1834 [Tipulidae]; Pachystylum Macquart, 1848 [Tachinidae]; Physegaster Macquart, 1847 [Acroceridae]; Plesionevra Macquart, 1855 [Tachinidae]; Rhopalia Macquart, 1838 [Mydidae]; Semiomyia Macquart, 1848 [Tachinidae]; Senostoma Macquart, 1847 [Tachinidae]; Silbomyia Macquart, 1844 [Calliphoridae]; Sumpigaster Macquart, 1855 [Tachinidae]; Tapinocera Macquart, 1838 [Apioceridae]; Teretrophora Macquart, 1851 [Tachinidae]; Toxocnemis Macquart, 1855 [Tachinidae]; Toxotarsus Macquart, 1851 [Calliphoridae]; Trichostylum Macquart, 1851 [Tachinidae]; Trigonometopus Macquart, 1835 [Lauxaniidae]; Tritaxys Macquart, 1847 [Tachinidae]; Vermileo Macquart, 1834 [Vermileonidae]. Acting as First Reviser, the following correct original spellings for multiple original spellings are selected by us—(for genus-group names): Choeteprosopa Macquart, 1851 [Tachinidae]; Dichoetometopia Macquart, 1855 [Sarcophagidae]; Discocerina Macquart, 1835 [Ephydridae]; Dolichocephala Macquart, 1823 [Empididae]; Dolichomerus Macquart, 1850 [Syrphidae]; Graphalostylum Macquart, 1851 [Tachinidae]; Hemilampra Macquart, 1850 [Syrphidae]; Leptomyza Macquart, 1835 [Anthomyzidae]; Microcheilosia Macquart, 1855 [Tachinidae]; Phrissopodia Macquart, 1835 [Sarcophagidae]; Platytainia Macquart, 1851 [Tachinidae]; Polychaeta Macquart, 1851 [Tachinidae]; Stachynia Macquart, 1835 [Conopidae]—(for species-group names): Cadicera rubramarginata Macquart, 1855 [Tabanidae]. Previous First Reviser actions for multiple original spellings that were missed by other workers are given for the following: Amethysa Macquart, 1835 [Ulidiidae]; Anabarhynchus Macquart, 1848 [Therevidae]; Anacanthella Macquart, 1855 [Stratiomyidae]; Aulacigaster Macquart, 1835 [Aulacigastridae]; Cardiacera Macquart, 1847 [Pyrgotidae]; Comptosia Macquart, 1840 [Bombyliidae]; Craspedia Macquart, 1838 [Asilidae]; Cyclorhynchus Macquart, 1840 [Bombyliidae]; Ectinorhynchus Macquart, 1850 [Therevidae]; Euthinevra Macquart, 1836 [Hybotidae]; Gonistylum Macquart, 1851 [Tachinidae]; Heterostylum Macquart, 1848 [Bombyliidae]; Hoplistomera Macquart, 1838 [Asilidae]; Hystricephala Macquart, 1846 [Tachinidae]; Leptoxyda Macquart, 1835 [Tephritidae]; Nemopalpus Macquart, 1838 [Psychodidae]; Senotainia Macquart, 1846 [Sarcophagidae]; Spilogaster Macquart, 1835 [Muscidae]; Spogostylum Macquart, 1840 [Bombyliidae]; Stachynia Macquart, 1835 [Conopidae]. Invoking ICZN Code Article 33.3.1, the following is here considered a correct original spelling by being in prevailing usage: Leptopeza Macquart, 1828 [Empididae]. Reversal of Precedence (ICZN Code Article 23.9) is invoked to promote stability in nomenclature for the following cases of subjective synonymy: Atherigona Rondani, 1856, nomen protectum and Orthostylum Macquart, 1851, nomen oblitum [in Muscidae]; Clusiodes Coquillett, 1904, nomen protectum and Heteronevra Macquart, 1835, nomen oblitum [in Clusiidae]; Senotainia Macquart, 1846, nomen protectum and Megoera Macquart, 1834, nomen oblitum [in Sarcophagidae]. The following genus-group names, not listed in current regional catalogs, are treated here: Diasema Macquart, 1835 [Chloropidae]; Dichromyia Macquart, 1844 [Heleomyzidae]; Elomyia Macquart, 1834 [Tachinidae]; Eriosoma Macquart, 1838 [Acroceridae]; Eurypalpus Macquart, 1835 [Platystomatidae]; Notacanthina Macquart, 1835 [Ephydridae]; Pleurocerina Macquart, 1851[Conopidae]; Pteropexus Macquart, 1846 [Acroceridae]; Semiomyia Macquart, 1848 [Tachinidae]; Teremyia Macquart, 1835 [Lonchaeidae]. The following names are new synonymies of their respective senior synonyms: —genus-group names: Acemyia Macquart, 1834 of Acemya Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Acrochoeta Macquart, 1835 of Acrochaeta Wiedemann, 1830, n. syn. [Stratiomyidae]; Atractea Agassiz, 1846 of Atractia Macquart, 1838, n. syn. [Asilidae]; Aulacocephala Brauer, 1863 of Aulacephala Macquart, 1851, n. syn. [Tachinidae]; Beckeriella Williston, 1897 of Notacanthina Macquart, 1834, n. syn. [Ephydridae]; Caenosia Macquart, 1835 of Coenosia Meigen, 1826, n. syn. [Muscidae]; Ceromyia Macquart, 1834 of Ceromya Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Chiromysa Macquart, 1835 of Chiromyza Wiedemann, 1820, n. syn. [Stratiomyidae]; Chrisochlora Macquart, 1835 of Chrysochlora Latreille, 1829, n. syn. [Stratiomyidae]; Chrysopyla Macquart, 1840 of Chrysopilus Macquart, 1826, n. syn. [Rhagionidae]; Cleigaster Macquart, 1844 of Cleigastra Macquart, 1835, n. syn. [Scathophagidae]; Clyto Macquart, 1835 of Clytho Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Cordylura Macquart, 1835 of Cordilura Fallén, 1810, n. syn. [Scathophagidae]; Craspedochaeta Marschall, 1873 of Anthomyia Meigen, 1803, n. syn. [Anthomyiidae]; Cyrtonevra Agassiz, 1846 of Graphomya Robineau-Desvoidy, 1830, n. syn. [Muscidae]; Diaphora Macquart, 1834 of Diaphorus Meigen, 1824, n. syn. [Dolichopodidae]; Dichoeta Macquart, 1835 of Dichaeta Meigen, 1830, n. syn. [Ephydridae]; Dichromyia Macquart, 1844 of Dichromya Robineau-Desvoidy, 1830, n. syn. [Heleomyzidae]; Diphysa Macquart, 1838 of Archistratiomys Enderlein, 1913, n. syn. [Stratiomyidae]; Echinomyia Fischer von Waldheim, 1808 of Tachina Meigen, 1803, n. syn. [Tachinidae]; Egina Macquart, 1835 of Eginia Robineau-Desvoidy, 1830, n. syn. [Muscidae]; Hematobia Macquart, 1850 of Haematobia Le Peletier & Audinet-Serville, 1828, n. syn. [Muscidae]; Hemerodromyia Macquart, 1823 of Hemerodromia Meigen, 1822, n. syn. [Empididae]; Heteronevra Macquart, 1835 of Clusiodes Coquillett, 1904, n. syn. [Clusiidae]; Himastima Agassiz, 1846 of Mallota Meigen, 1822, n. syn. [Syrphidae]; Hoematopota Macquart, 1826 of Haematopota Meigen, 1803, n. syn. [Tabanidae]; Homalocephala Agassiz, 1846 of Setellia Robineau-Desvoidy, 1830, n. syn. [Sciomyzidae]; Hydrotoea Macquart, 1844 of Hydrotaea Robineau-Desvoidy, 1830, n. syn. [Muscidae]; Linnemyia Macquart, 1834 of Linnaemya Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Lonchoea Macquart, 1835 of Lonchaea Fallén, 1820b, n. syn. [Lonchaeidae]; Macromyia Macquart, 1835 of Macromya Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Megarhina Macquart, 1838 of Lynchiella Lahille, 1904, n. syn. [Culicidae]; Meriana Macquart, 1835 of Panzeria Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Microphorus Lundbeck, 1907 of Microphor Macquart, 1834, n. syn. [Dolichopodidae]; Nemoroea Macquart, 1844 of Nemoraea Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Ochthiphila Macquart, 1850 of Chamaemyia Meigen, 1803, n. syn. [Chamaemyiidae]; Ocydromyia Macquart, 1823 of Ocydromia Meigen, 1820, n. syn. [Hybotidae]; Oliviera Macquart, 1835 of Eriothrix Meigen, 1803, n. syn. [Tachinidae]; Ophilia Macquart, 1850 of Metopia Meigen, 1803, n. syn. [Sarcophagidae]; Ornithomyia Fischer von Waldheim, 1808 of Ornithomya Latreille, 1802, n. syn. [Hippoboscidae]; Orthochile Westwood, 1840 of Ortochile Latreille, 1809, n. syn. [Dolichopodidae]; Osmoea Macquart, 1834 of Triarthria Stephens, 1829, n. syn. [Tachinidae]; Pachyrrhina Osten Sacken, 1878 of Pachyrhina Macquart, 1834, n. syn. [Tipulidae]; Palis Macquart, 1850 of Pales Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Phanemia Macquart, 1835 of Clairvillia Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Phrissopoda Macquart, 1851 of Peckia Robineau-Desvoidy, 1830, n. syn. [Sarcophagidae]; Phyllomyia Macquart, 1834 of Phyllomya Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Physogenia Loew, 1862 of Physegenua Macquart, 1848, n. syn. [Lauxaniidae]; Physogenua Giglio-Tos, 1895 of Physegenua Macquart, 1848, n. syn. [Lauxaniidae]; Phytomiza Macquart, 1835 of Phytomyza Fallén, 1810, n. syn. [Agromyzidae]; Platipalpus Macquart, 1850 of Platypalpus Macquart, 1828, n. syn. [Hybotidae]; Platipeza Macquart, 1850 of Platypeza Meigen, 1803, n. syn. [Platypezidae]; Platynochoetus Macquart, 1834 of Platynochaetus Wiedemann, 1830 [Syrphidae]; Porphirops Macquart, 1838 of Porphyrops Meigen, 1824, n. syn [Dolichopodidae]; Rhinomyia Macquart, 1835 of Rhinomya Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Rhynomyia Macquart, 1834 of Rhinomya Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Scathopse Guérin-Méneville, 1839 of Scatopse Geoffroy, 1762, n. syn. [Scatopsidae]; Spherophoria Macquart, 1850 of Sphaerophoria Le Peletier & Audinet-Serville, 1828, n. syn. [Syrphidae]; Sphoerophoria Macquart, 1829 of Sphaerophoria Le Peletier & Audinet-Serville, 1828, n. syn. [Syrphidae]; Stenopteryx Schiner, 1864 of Stenepteryx Leach, 1817, n. syn. [Hippoboscidae]; Stenostoma Mik, 1890 of Senostoma Macquart, 1847, n. syn. [Tachinidae]; Tachydromyia Macquart, 1823 of Tachydromia Meigen, 1803, n. syn. [Hybotidae]; Taenioptera Mik, 1898 of Taeniaptera Macquart, 1835, n. syn. [Micropezidae]; Trinevra Macquart, 1835 of Phora Latreille, 1797, n. syn. [Phoridae]; Uramyia Macquart, 1844 of Uramya Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Xestomysa Macquart, 1851 of Xestomyza Wiedemann, 1820, n. syn. [Therevidae]; Zygonevra Macquart, 1834 of Zygoneura Meigen, 1803, n. syn. [Sciaridae]. —Species-group names: Calobatemyia nigra Macquart, 1855 of Musca doronici Scopoli, 1763, n. syn. [Calliphoridae]; Cyrtonevra protorum Macquart, 1850 of Musca pratorum Meigen, 1826, n. syn. [Muscidae]; Eumerus oeneus Macquart, 1850 of Eumerus aeneus Macquart, 1829, n. syn. [Syrphidae]; Lucilia ceserion Macquart, 1850 of Musca caesarion Scharfenberg, 1805, n. syn. [Calliphoridae]; Masicera sylvatica Macquart, 1850 of Tachina silvatica Fallén, 1810, n. syn. [Tachinidae]; Ophyra anolis Macquart, 1850 of Ophyra analis Macquart, 1846, n. syn. [Muscidae]; Pegomyia hyosciami Macquart, 1850 of Musca hyoscyami Panzer, 1798, n. syn. [Anthomyiidae]; Prosena syberita Macquart, 1850 of Stomoxys siberita Fabricius, 1775, n. syn. [Tachinidae]; Taxigramma heteronevra Macquart, 1850 of Miltogramma heteroneura Meigen, 1830, n. syn. [Sarcophagidae].